HEMORRHAGIC CYSTITIS IN MALE LOCAL CATS - Saputra, Andri; Jayanti, Putu Devi; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2025)
Cystitis is an inflammation of the bladder that often occurs in cats, as part of a urinary tract infection. This study aims to provide treatment and healing treatment for cystitis. This study used a local male cat weighing 4.4 kg, aged 1 year who complained of not wanting to eat, weakness, difficulty urinating for three days, and experiencing blood in the urine for a week. The study used a descriptive analysis method. The results showed that the cat suffered from cystitis based on clinical signs, urine dipstick examination, sedimentation and ultrasound. Treatment for the case animals consisted of 0.9% NaCl infusion fluid therapy 558 mL/day for 2 days, urinary catheter installation for 4 days. Ciprolaxacin (5 mg/kg BW, orally (PO), q12h), methylprednisolone (4 mg/kg BW, orally (PO), q24h), Samylin 1 tablet once a day for 10 days. nephrolite 1 capsule once a day for 10 days. Cats experienced changes after being given therapy for ten days marked by smooth urination without stranguria, dysuria, and hematuria during urination. The results of the study showed healing in animals with cystitis.